Desarrollo de un panel aislante térmico y acústico a partir de cáscaras de huevo y almidón de maíz para la construcción - Lee Saltos, Victor Do-win (2024)
In a context marked by a growing interest in ecological solutions for the construction industry, the construction sector is currently faced with the challenge of finding solutions that minimize its environmental impact. This study focuses on harnessing the unique properties of natural resources to develop a thermoacoustic panel that enhances both thermal and acoustic insulation. Through a series of experiments and analyses, the goal is to effectively combine these elements to create an alternative material that reduces energy demand in buildings and enhances people's quality of life. This innovative approach has the potential to contribute significantly to the field of sustainable construction by utilizing renewable resources and by-products of the food industry in the pursuit of environmentally friendly solutions. Given the need to find alternatives to reduce poultry waste and utilize it in the construction industry, the creation of a panel from main elements such as eggshell and cornstarch is proposed, thereby driving ecological solutions.........